Prioritising transplantation for adult congenital heart disease, UK national data. (15th May 2020) - Burch, Michael; Taylor, Amy; Mehew, Jennifer; Dominguez, Troy; Crossland, David; Lewis, Clive; Taylor, Rhiannon; Clift, Paul; Al-Attar, Nawwar; Venkateswaran, Rajamiyer; Banner, Nicholas
Abstract: Objective: There are no multi-centre data on the outcomes of transplant for adult congenital heart disease (ACHD) outside of North America. The literature has identified a number of concerns for this population such as increased wait-list and early post-operative mortality. We investigated outcomes in a national cohort to see if these problems are replicated outside of America. Methods: Adults (aged ≥16 years) undergoing primary heart transplantation 1995–2014 were identified in the UK Registry and registration, operative and post-transplantation related clinical factors were compared to non ACHD recipients. Results: Of 3026 adults who underwent primary heart transplantation, 134 (4.4%) had ACHD (median age 30 years; 40.3% female). For the ACHD patients listed as urgent status, the time to transplant was not significantly different to non ACHD patients and ACHD were not more likely to die or be removed from the wait list. Despite ACHD recipients having longer hospital stays (27 vs. 22 days; p = 0.003) and worse 90-day survival (79.5% vs. 86.6%; p = 0.02), long-term post-transplantation survival was not significantly different. Creatinine clearance was significantly better in ACHD patients at follow-up. In the last 10 years of our study period, all single ventricle transplants have been restricted to experienced ACHD teams, one year survival for Fontan patients was 89.5%. Conclusions: The use of urgent listing appears to have benefited the ACHD group by allowing equal access to transplantation, and recent concentration of expertise for single ventricle transplants has been associated with excellent early survival. Highlights: We report the UK data for adult congenital heart disease. Time to transplant was not significantly different to other heart transplants. Despite longer hospital stays long-term post-transplantation survival was similar. Creatinine clearance was significantly better. Single ventricle transplants were centralised to experienced ACHD centres.